Epic video games: Narrative spaces and engaged lives. (September 2016) - Zarzycki, Andrzej
Contemporary video games such as Mass Effect or Assassin's Creed are emerging as a new form of media departing from traditional games purely seen as problem-solving exercises. They represent a new creative direction enjoyed by a broader audience, similar to those of TV and cinema. At the same time, they are significantly different from TV and cinema, since they place the user at the center of interactions, allowing content creation and forming strong emotional bonds. This article discusses the role of narratives in these new epic games as the main driver behind their social appeal and commercial success. It also poses a number of questions in the context of architecture and the possible fusion of both architecture and narrative.